Injuries caused by freshwater stingrays in the Tapajos River Basin: a clinical and sociodemographic study - Martins Abati, Paulo Afonso; Quispe Torrez, Pasesa Pascuala; Siqueira Franca, Francisco Oscar de; Tozzi, Fabio Lambertini; Bacelar Guerreiro, Flavio Mileo; Torres dos Santos, Suellen Aline; Silva de Oliveira, Sheyla Mara; Haddad Junior, Vidal [UNESP] (Soc Brasileira Medicina Tropical, 2017)
Freshwater stingray envenomations are an important cause of morbidity in riverine populations living in various regions of Brazil. The sequelae include temporary or permanent disability. This study aimed to identify sociodemographic, clinical, and therapeutic aspects related to stingray injuries in such populations. Methods: This cross-sectional study was conducted in the Extractive Reserve of Tapajos-Arapiuns, located in the municipalities of Santarem and Aveiro (Para State). A convenience sample comprising 300 local adults was used to obtain data by means of a questionnaire/interview. Results: Overall, 19 (6.3%) participants reported having sustained a stingray injury in the 12 months prior to the study. All 19 were injured either while fishing (n=13 [68.4%]) or engaging in other riverine activities. Most injuries [n=14 (73.7%)] occurred from September through November, and most injured respondents [n=15 (78.9%)] reported seeing stingrays at beaches. Severe pain and the appearance of ulcers in the later stages of envenomation were described by 18 (94.7%) and 12 (63.2%) participants, respectively. Conclusions: Freshwater stingray injuries, which should be considered occupational injuries, are common in the study area, especially in places like beaches or in the lakes that form during the dry season, when stingrays are routinely observed. A significant proportion of respondents was unaware of the correct first aid measures and had insufficient resources to treat the complications of these injuries in the locality where they reside. Interactive activities involving local residents - such as lectures and the distribution of simple pamphlets providing information about stingray injuries - are needed.
Keywords: Stings; Venomous animals; Freshwater stingrays; Potamotrygonidae; Amazon region